Uso de videojuegos y conductas agresivas en adolescentes. - Cárdenas Rivadeneira, Cristopher Emmanuel (2025)
Video game usage is a common activity among adolescents. When these games feature violent content, concerns arise regarding their potential influence on the emergence or intensification of aggressive behaviors during this developmental stage. This research aimed to analyze the relationship between video game use and aggressive behaviors in adolescents through a literature review of studies published between 2015 and 2025. A bibliographic documentary methodology was employed, with a descriptive level and a non-experimental design, applying the PRISMA protocol for the systematic selection of sources. The search was conducted in specialized databases (Scopus, Web of Science, PubMed, ProQuest, and Dialnet) using Boolean operators and key terms in both Spanish and English. After applying relevance filters and assessing methodological quality with the CRF-QS instrument, 17 studies were included in the final analysis. The results indicated that studies report a positive association between violent video games and aggressive behaviors, specifically within physical aggression and anger dimensions. It is concluded that a significant relationship exists among these variables, although aggression expression varies according to the adolescent's profile and social context.